The Impact Of Digital Service And Innovative Work Behavior On Employee Performance : The Mediating Role Of Job Satisfaction - Harsaningsih, Harsaningsih; Sulistyowati, Indah; Isnaeni, Yuli; Sukandar, Agus; Mursid, Ali (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study investigates "The Impact of Digital Service and Innovative Work Behavior on Employee Performance: The Mediating Role of Job Satisfaction." It aims to explore how Digital Service and Innovative Work Behavior influence Employee Performance, with Job Satisfaction acting as a mediating variable. Theresearch proposes five hypotheses: H1 posits that Digital Service positively affects Job Satisfaction; H2 suggests that Digital Service enhances Employee Performance; H3 indicates that Innovative Work Behavior positively influences Job Satisfaction; H4 asserts that Innovative Work Behavior improves EmployeePerformance; and H5 evaluates the mediating effect of Job Satisfaction on the relationships between Digital Service, Innovative Work Behavior, and Employee Performance. Using a questionnaire distributed to 200 respondents, this study seeks to provide valuable insights into the interconnectedness of these factors and their collective impact on enhancing employee performance.